Pelaksanaan Ekstrakurikuler Marching Band Di MAN 3 Padang - Dodi Febrian; Syeilendra Syeilendra (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to describe the extracurricular implementation of marching band in Man 3 Padang until now. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by observation, literature study, interviews and documentation. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that the implementation of the Marching Band Extracurricular at MAN 3 Padang had taken place 4 times with a number of challenges faced. There are some drawbacks to note. One of them is the inconsistent absence of members at each meeting. The absence of members at some meetings affects the uniformity of understanding of the material, and absent members have to catch up with delays in understanding the material that has been delivered. At some meetings, there are a number of members who are absent without clear information, which can have an impact on the smooth implementation of the exercise. Technical obstacles also arise in the implementation such as in the song Indonesia Raya, the distance between the notations on the pianika played far away so that the pianika played by students who play on the pianika instrument delay / late produced and the song Mengheningkan Cipta percussion members play an unstable tempo because the tempo in the song is slow.